Partner-Mediated Polymorphism of an Intrinsically Disordered Protein. Issue 16 (3rd August 2018) - Bignon, Christophe; Troilo, Francesca; Gianni, Stefano; Longhi, Sonia
Abstract: Intrinsically disordered proteins (IDPs) recognize their partners through molecular recognition elements (MoREs). The MoRE of the C-terminal intrinsically disordered domain of the measles virus nucleoprotein (NTAIL ) is partly pre-configured as an α-helix in the free form and undergoes α-helical folding upon binding to the X domain (XD) of the viral phosphoprotein. Beyond XD, NTAIL also binds the major inducible heat shock protein 70 (hsp70). So far, no structural information is available for the NTAIL /hsp70 complex. Using mutational studies combined with a protein complementation assay based on green fluorescent protein reconstitution, we have investigated both NTAIL /XD and NTAIL /hsp70 interactions. Although the same NTAIL region binds the two partners, the binding mechanisms are different. Hsp70 binding is much more tolerant of MoRE substitutions than XD, and the majority of substitutions lead to an increased NTAIL /hsp70 interaction strength. Furthermore, while an increased and a decreased α-helicity of the MoRE lead to enhanced and reduced interaction strength with XD, respectively, the impact on hsp70 binding is negligible, suggesting that the MoRE does not adopt an α-helical conformation once bound to hsp70. Here, by showing that the α-helical conformation sampled by the free form of the MoRE does not systematically commit it to adopt an α-helical conformation in the bound form, we provide an example of partner-mediated polymorphism of an IDP and of the relative insensitiveness of the bound structure to the pre-recognition state. The present results therefore contribute to shed light on the molecular mechanisms by which IDPs recognize different partners. Graphical Abstract: Image 1 Highlights: IDPs may adopt a different fold depending on the partner to which they bind. NTAIL binds to both XD and hsp70 and undergoes α-helical folding upon binding to XD. NTAIL binds the two partners using the same region but different residues and adopts a different fold. Variation in NTAIL helicity has a markedly different impact on hsp70 and XD binding. The affinity for hsp70, but not that for XD, can be increased by rational mutagenesis. The pre-recognition state of an IDP does not systematically presage of its bound form.